A Estabilidade Transiente de Sistemas Elétricos na Presença de Geradores Síncronos Virtuais: Metodologias de Análise e Controles Adaptativos - Carletti, Daniel (2020)
The dynamic stability assessment of electrical power systems is an activity of utmost importance to guarantee the energy delivery to consumers in a safe and stable way. The study of transient stability, which deals with maintaining the generation plants i